Janicki’s Love for the Homeland and His Patriotic Poetry: Tribute on the 500th Anniversary of the Poet’s Birthday (1516–1543) - Lewandowski, Ignacy (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The paper aims to present some aspects of Janicki’s poetry devoted to some Various existence problems of that times, i. e. social status of the poor, the education opportunities for them, and insisting on the greater care of the country from the nobility